Padrões geográficos de ancestralidade genômica em Minas Gerais: o caso da doença falciforme - Maria Clara Fernandes da Silva Malta (2010)
Admixture occurs when individuals from parental populations that have been isolated for hundreds of generations, form a new hybrid population. The interest in estimating admixture is critical in genetic epidemiology studies in admixed populations, since stratification generated by admixture can lead to false-positive associations. Markers with highly differentiated frequencies among human populations are especially informative for estimating admixture and are called Ancestry Informative Markers (AIMs). We present two multiplex panels of AIMs (for a total of 14 SNPs) developed to be genotyped by two mini-sequencing reactions. We tested the performance of these AIMs by comparing results obtained using our 14 AIMs with those obtained using 108 AIMs genotyped in the same individuals. At population level, our 14 AIMs are useful to estimate European admixture, but overestimate African admixture and underestimate Native American admixture. In performance tests, the addition of genotyping results for 40 INDELs, previously validated to capture the structure of human populations, improved the estimative of admixture both at individual and population levels. These panels of 14 SNPs and 40 INDELs were used to estimate admixture in subjects with sickle cell disease (n = 200) and healthy individuals, blood donors (n = 291), sampled in different regions of the state of Minas Gerais. The results point to an intense admixture in both groups, although a higher African admixture was observed among patients. Variations in levels of admixture between the different regions of Minas Gerais, as well as among individuals sampled in each region, were observed for both patients and donors. These results warn of the risk of spurious associations in genetic epidemiology studies with case-control design, involving these groups. Moreover, the finding that patients with sickle cell disease have substantial levels of admixture opens the perspective for the use of admixture mapping strategy in the investigation of genetic polymorphisms associated with different clinical manifestations of this disease